General relativistic dynamics:extending Einstein's legacy throughout the Universe - Cooperstock Fred I (World Scientific, 2009)
This book brings Einstein's general relativity into action in new ways at scales ranging from the tiny Planck scale to the scale of immense galactic clusters. It presents the case that Einstein's theory of gravity can describe the observed dynamics of galaxies without invoking the unknown ?dark matter? required in models based on Newtonian gravity.
Keywords: General relativity -Physics; Gravitational fields; Gravity